PEMANFAATAN INFORMASI AKUNTANSI UNTUK MENGHINDARI ESKALASI KOMITMEN PADA LEVEL PENGAMBILAN KEPUTUSAN (Studi pada Mahasiswa Akuntansi PTN dan PTS se Kota Jambi) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The Objective of this research is to examine accounting information as strategy to helpdecision maker avoiding escalation of commitment. Given strategy include unambiguousfeed back strategy, project progress report, and giving information of future advantage toindividual or group of decision maker. Sums of 130 students of Accounting Department,Faculty of Economic, Jambi University participate in this experiment. The result of the testshows that the three strategies can significantly help decision maker avoiding commitmentescalation problem. However, surprisingly the result of the test show that strategy to givefuture benefit information significantly tends to direct the group to commitment escalation.The test is also performed to observe whether there is polarization of individual or groupdecision. Statistic results give support that when the three strategies are given to individualand group of decision maker and group polarization occurred.Keywords : escalation of commitment, accounting information strategy, individual-groupdecision